2017
DOI: 10.1002/adhm.201600860
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Bonding of RGD and YIGSR to an Electrospun Poly(ε‐Caprolactone) Conduit through Peptide Self‐Assembly to Synergistically Promote Sciatic Nerve Regeneration in Rats

Abstract: The nerve conduit with biofunctionalities can regulate neurite outgrowth, as well as the migration, proliferation, and myelination activity of Schwann cells. In the present study, polycaprolactone (PCL) conduits are coated with Naphthalene-phenylalanine-phenylalanine-glycine-arginine-glycine-aspartic (Nap-FFGRGD) and Naphthalene-phenylalanine-phenylalanine-glycine-cysteine-aspartic-proline-glycine-tyrosine-isoleucine-glycine-serine-arginine (Nap-FFGCDPGYIGSR) by self-assembly. In vitro studies demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 63 publications
1
48
2
Order By: Relevance
“…Also, it has been shown that a PCL conduit can improve motor functional recovery by increase in sciatic functional index (SFI) values, recovery in muscle atrophy, and increase in number of regenerated axons in the sciatic nerve gaps due to creating proper porosity and increase of vascularization in the implanted site (Pixley et al, ; Zhu et al, ). Therefore, this polymer can be considered as one of the most suitable candidates for fabricating the neural conduit.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…Also, it has been shown that a PCL conduit can improve motor functional recovery by increase in sciatic functional index (SFI) values, recovery in muscle atrophy, and increase in number of regenerated axons in the sciatic nerve gaps due to creating proper porosity and increase of vascularization in the implanted site (Pixley et al, ; Zhu et al, ). Therefore, this polymer can be considered as one of the most suitable candidates for fabricating the neural conduit.…”
Section: Materials For Fabricating Nerve Conduitsmentioning
confidence: 99%
“…The application of electrospun scaffolds extends to both peripheral nerve injury, and central nervous system injury,[28a,167] which consists of traumatic brain injury168 and spinal cord injury. [33b,91,169] Those neurodegenerative diseases and traumatic nerve injuries vastly deteriorate the life quality and proper treatment methods are yet missing.…”
Section: Applications In Biomedical Fieldsmentioning
confidence: 99%
“…Aiming for bridging the defected nerve with a gap larger than 10 mm, Zhu et al produced a tubular PCL nerve conduit composed of electrospun microfibers. Peptide self‐assembled RGD and YIGSR layers were non‐covalently bonded to the obtained PCL fibers and were expected to improve the biocompatibility of hydrophobic PCL fibers ( Figure a,b).…”
Section: Applications In Biomedical Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…This team concluded that PCL scaffolds may be improved by the use of RGD/YIGSR peptides. 25 One of the possible modifications of the electrospinning technique is the fabrication of a layered scaffold, which can regulate degradation time and improve mechanical/biological properties. Chung J et al in 2014 made tubular scaffolds of three layers: internal and external layers made of polycaprolactone and a middle layer made of silk fibroin.…”
Section: Modified Polycaprolactonementioning
confidence: 99%